(untitled) (Experimental biology, 2015)
One of the cheapest and effective methods of harmful effect of mining-and-metallurgical industry toxic wastes limitation on the environment is phytoconservation. The using of «Bios-Phyto TM» preparation in this technology has the following results: 1. it raises the project cover indexes of toxic wastes dust surfaces by plant mass; 2. the compound supplementation of this preparation with local flora dominant species allows to use phytoconservation technology in every region of Kazakhstan.